Piloting a collaborative data library of fine-grained data to support knowledge facilitation in architectural courses. Issue 5 (November 2020) - Thuvander, L; Green, C; Adelfio, M; Brandao, E; Combrinck, C; Billger, M; Rautenbach, V; Coetzee, S; Plessis, C du
Abstract: This study discusses the establishment and pilot of a collaborative data library (CDL) for educational purposes, based on a transdisciplinary collaboration between the architecture departments at Chalmers University of Technology in Gothenburg, Sweden, and University of Pretoria, South Africa. The CDL was tested Hammarkullen in Gothenburg in a joint exercise during which students from both institutions collected qualitative and quantitative data through site analysis using analogue and digital tools such as KoboToolbox and Maptionnaire. The collected data were uploaded in guided sessions to the web-based platform GeoNode to be stored in a systematic way for re-use of the data later in the course. Results show that the tools and CDL were relatively easy to use. For the students the most interesting aspects were the contextual information gained by using the data collecting tools, and, by that, make communities' needs heard. Thus, the students appreciated the participatory features of the data collection tools. The CDL will be further developed and tested in the South African design studio in the Mamelodi township of Pretoria early in 2020. The development of the CDL in a transdisciplinary and global context will allow for up-scaling and potentially also applications outside educational environments. The project contributes to the United Nations' Sustainable Development Goals 4 and 11.